GESTURES FOR LEARNING VOCABULARY TOWARDS STUDENTS’ SPECIAL NEEDS (DEAF): Gestures For Learning Vocabulary Towards Students' Special Needs (Deaf) - Toninel, Mega Fransiska; Sahib, Nurfaizah; Syam, Ulfah (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
English has become important in the 4.0 era since numerous electronic devices, such as medical equipment for doctors or salespeople who interact with foreigners in malls, have English conditions. Because of the various cultures that continue to enter Indonesia, ordinary as well as oustanding school systems must learn more about English by expanding their English vocabulary, especially for students special needs, and sign language is employed as a teaching tool in exceptional schools. The purpose of this research is to learn gestures for vocabulary learning for students special needs (deaf), specifically eleventh-grade students at SLB-B YPPLB Makassar. The research method used was qualitative. The responses from observations, questionnaire sheets, and interview sessions have been reviewed by the researcher. According to the data, the first, SIBI, was used in vocabulary learning for students at the Makassar YPPLB SLB-B school because it was less complicated and better organized. Second, it could be concluded that the teacher's influence was indeed important for students, but student interaction was actually very influential on the mood and enthusiasm of students when learned in class, and the third was that using video was ineffective for them to learn because it was difficult for them to understand.